Chronic FLT3-ITD Signaling in Acute Myeloid Leukemia Is Connected to a Specific Chromatin Signature - Cauchy, Pierre; James, Sally R.; Zacarias-Cabeza, Joaquin; Ptasinska, Anetta; Imperato, Maria Rosaria; Assi, Salam A.; Piper, Jason; Canestraro, Martina; Hoogenkamp, Maarten; Raghavan, Manoj; Loke, Justin; Akiki, Susanna; et al. (Cell reports (Cambridge), 2015)
Acute myeloid leukemia (AML) is characterized by recurrent mutations that affect the epigenetic regulatory machinery and signaling molecules, leading to a block in hematopoietic differentiation. Constitutive signaling from mutated growth factor receptors is a major driver of leukemic growth, but how aberrant signaling affects the epigenome in AML is less understood. Furthermore, AML cells undergo extensive clonal evolution, and the mutations in signaling genes are often secondary events. To elucidate how chronic growth factor signaling alters the transcriptional network in AML, we performed a system-wide multi-omics study of primary cells from patients suffering from AML with internal tandem duplications in the FLT3 transmembrane domain (FLT3-ITD). This strategy revealed cooperation between the MAP kinase (MAPK) inducible transcription factor AP-1 and RUNX1 as a major driver of a common, FLT3-ITD-specific gene expression and chromatin signature, demonstrating a major impact of MAPK signaling pathways in shaping the epigenome of FLT3-ITD AML. [Display omitted] •FLT3-ITD signaling is associated with a common gene expression signature•FLT3-ITD-specific gene expression is associated with a common chromatin signature•FLT3-ITD AML displays chronic activation of the inducible transcription factor AP-1•AP-1 cooperates with RUNX1 to shape the epigenome of FLT3-ITD AML Cauchy et al. identify a specific gene expression and regulatory signature associated with aberrant signaling in acute myeloid leukemia with FLT3-ITD mutations. In FLT3-ITD AML, the inducible transcription factor AP-1 is chronically activated and cooperates with RUNX1, shaping the epigenome to transactivate specific target genes.